KEBIJAKAN JAMINAN FIDUSIA PADA PEMBIAYAAN MURABAHAH DI BANK SYARIAH MANDIRI KANTOR CABANG PEMBANTU MERDEKA BOGOR - Sholihin, Irfan Taufik; Thantawi, T Rifqy (NISBAH: JURNAL PERBANKAN SYARIAH, 2018)
In the practice of providing financing by Bank Syariah, fiduciary guarantee becomes a very calculated object in the trial. Because fiduciary security is processed through a notary and witnessed by legal persons. There is also the posibility of problems related to the implemntation of teh financing agreement with fiduciary guarantee concerning the decrease of the selling price after teh aution is condccted by the Sharia Bank.The research method that will be used by the researcher is case study or case study, with the research specification used is descriptive qualitative.The results of this study can be conclded tht the implemntation of fiduciary guarantee policy in Syariah Mandiri Bank Branch Merdeka Bogor branch that the financing above Rp. 100.000.000 is required to use fiduciary guarantee, while for under Rp.100.000.000, for example Rp.70.000.000 depemding on the result of meeting, whether approved to get fiduciary guarantee or not.